Reaching 5.0×10-13τ-1/2 short term frequency stability of the integrating sphere cold atom clock. (June 2016) - Liu, P; Meng, Y L; Wan, J Y; Wang, X M; Wang, Y N; Xiao, L; Cheng, H D; Liu, L
Abstract: We present an improvement of short term frequency stability of the integrating sphere cold atom clock after increasing the intensities of clock signals and optimizing the feedback loop of the clock. A short term frequency stability of 5.0×10 -13 τ -1/2 has been achieved and the limiting factors have been analyzed.